2016
DOI: 10.1097/01.asw.0000494779.66288.c9
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Ulcers in the Intensive Care Unit: An Analysis of Skin Barrier Risk Factors

Abstract: Nursing strategies aimed at preventing PrUs should place added emphasis on the lower sacral and hip regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…In other studies conducted in non-specialized Brazilian ICUs (4)(5)(6)(7)(8) , the overall cumulative incidence of PI was lower, varying between 3.5% and 23.1%. However, a study conducted in a Chinese ICU (also not specialized in oncology) found an overall cumulative PI incidence of 31.4%, similar to this study's (10) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In other studies conducted in non-specialized Brazilian ICUs (4)(5)(6)(7)(8) , the overall cumulative incidence of PI was lower, varying between 3.5% and 23.1%. However, a study conducted in a Chinese ICU (also not specialized in oncology) found an overall cumulative PI incidence of 31.4%, similar to this study's (10) .…”
Section: Discussionsupporting
confidence: 87%
“…This vulnerability is mainly due to advanced age, chronic diseases such as diabetes mellitus, mean arterial pressure < 60-70 mmHg, prolonged mechanical ventilation, continuous venovenous haemofiltration and/or intermittent dialysis, use of vasoactive drugs and/or sedatives, insufficient changes of patient position in bed, and length of stay in the ICU (2) . It is worth emphasizing that the incidence of PIs in ICUs is high, ranging from 11% to 37% (3)(4)(5)(6)(7)(8)(9)(10) . This indicates that PIs are a serious public health problem, which compromises patient safety and entails high health-system costs (11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…[5,24] ICU patients tend to be sedated, on mechanical ventilation and bed-bound for long periods. [25] Consequently, their physical activity is severely limited and their intake of nutrients is likely to be insufficient. [26] All of these factors could place ICU patients at greater risk of PU development.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study in China in 2016 showed that the prevalence of pressure injury development in the ICUs is 31%. 8 The development of pressure injury in hospitalized patients is considered as a negative point of healthcare providers and systems. Therefore, the prevention of pressure injury is highly important, especially for the nursing team.…”
Section: Introductionmentioning
confidence: 99%